2023
DOI: 10.1002/acr.25058
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Cutaneous Lupus Erythematosus After Twenty Weeks of Belimumab Use: A Systematic Review and Meta‐Analysis

Abstract: Objective Cutaneous lupus erythematosus (CLE), with or without systemic lupus erythematosus (SLE), can be debilitating and cause psychological distress. Belimumab, a monoclonal antibody that inhibits B cell activation, is a Federal Drug Administration–approved SLE medication, but less is known on its use in CLE. Moreover, the time to response after starting belimumab in CLE is unknown, which may lead to premature discontinuation in the absence of early perceivable benefits. Thus, the objectives of this meta‐an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…6 Belimumab, a monoclonal antibody that inhibits B cell survival factor B-lymphocyte stimulator, has only shown modest improvement in CLE and may take several months of treatment to show a clinical response. 7 Here, we showcase the clinical utility of anifrolumab in SCLE, and offer it as promising therapeutic option for patients who have failed belimumab, which is also supported by several case series. 3 , 4 , 5 Additionally, its rapid efficacy can prevent the irreversible damage associated with longstanding CLE including dyspigmentation and scarring which negatively impacts emotions and functioning of patients.…”
Section: Discussionsupporting
confidence: 64%
“…6 Belimumab, a monoclonal antibody that inhibits B cell survival factor B-lymphocyte stimulator, has only shown modest improvement in CLE and may take several months of treatment to show a clinical response. 7 Here, we showcase the clinical utility of anifrolumab in SCLE, and offer it as promising therapeutic option for patients who have failed belimumab, which is also supported by several case series. 3 , 4 , 5 Additionally, its rapid efficacy can prevent the irreversible damage associated with longstanding CLE including dyspigmentation and scarring which negatively impacts emotions and functioning of patients.…”
Section: Discussionsupporting
confidence: 64%
“…27 No safety signals were observed with regard to initiating or continuing belimumab treatment in patients with SLE or LN. 26,28 In this study, we found that treatment with belimumab was associated with a 27% reduction in the risk of serious TEAEs compared to placebo. In the belimumab group, the incidences of infectious TEAEs and death were not increased.…”
Section: Discussionmentioning
confidence: 61%
“…The safety of belimumab therapy in patients with LN is a major concern 27 . No safety signals were observed with regard to initiating or continuing belimumab treatment in patients with SLE or LN 26,28 . In this study, we found that treatment with belimumab was associated with a 27% reduction in the risk of serious TEAEs compared to placebo.…”
Section: Discussionmentioning
confidence: 66%
“…A small retrospective study in 73 patients with refractory CLE to first-line therapy found similar response rates (~65%) between MTX and mycophenolate 48. Anifrolumab and belimumab have both shown efficacy in mucocutaneous manifestations of SLE,49 50 although only anifrolumab has used the Cutaneous Lupus Area and Severity Index in its clinical programme, whereas belimumab has reported responses according to the general instruments SLEDAI and BILAG (hence, the designation B in the Grading of Recommendation, despite positive RCT data). Importantly, the list of recommended drugs is indicative and other treatments may be considered as second-line or third-line options, including dapsone, retinoids, CNI, AZA, CYC and RTX, ideally in collaboration with dermatologists experienced in the treatment of CLE.…”
Section: Resultsmentioning
confidence: 99%